2018
DOI: 10.1097/txd.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HLA Donor-Specific IgG Subclasses and C1q-binding Evolution in Posttransplant Monitoring

Abstract: BackgroundThe identification of low-level antibodies by single-antigen bead methodology has brought advancements to risk evaluation of kidney transplant recipients. However, the use of mean fluorescence intensity (MFI) to quantify antibodies and to guide therapy is not enough. Notably, immunoglobulin G (IgG) subclass switching is hypothesized to follow a programmed sequence after an emergency signal from the germinal center. In transplantation this process is not clear yet. In the present study, we sequentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Hence, high titers of strong C1q-binding subclasses, particularly IgG1, alone or combined with other IgG subclasses, mainly IgG2, may compose the hexamer formation to efficiently recruit the C1q protein. These results are in line with those recently reported by Ponsirenas et al (46), who, although without revealing the real-strength of IgG subclasses diluting serum-samples, found that C1q-binding was detected in high MFI antibodies comprised of IgG1 or multiple IgG subclasses. Only under certain conditions such as increased concentration of immunoglobulin, even IgG2 could effectively activate the complement (30).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, high titers of strong C1q-binding subclasses, particularly IgG1, alone or combined with other IgG subclasses, mainly IgG2, may compose the hexamer formation to efficiently recruit the C1q protein. These results are in line with those recently reported by Ponsirenas et al (46), who, although without revealing the real-strength of IgG subclasses diluting serum-samples, found that C1q-binding was detected in high MFI antibodies comprised of IgG1 or multiple IgG subclasses. Only under certain conditions such as increased concentration of immunoglobulin, even IgG2 could effectively activate the complement (30).…”
Section: Discussionsupporting
confidence: 93%
“…However, these assays do not distinguish between stronger complement‐fixing IgG1 and IgG3 subclasses from the lesser complement‐fixing IgG2 and IgG4, given that the detection reagent is specific for all Fcγ. Different routes of allosensitization trigger distinct patterns of IgG subclasses directed against HLA 33‐35 . Preliminary studies of HLA antibody subclasses suggest that IgG2 and IgG4 do not constitute a large proportion of HLA DSAs.…”
Section: Attributes Of Hla Antibodiesmentioning
confidence: 99%
“…Different routes of allosensitization trigger distinct patterns of IgG subclasses directed against HLA. [33][34][35] subclasses suggest that IgG2 and IgG4 do not constitute a large proportion of HLA DSAs. Rather, HLA IgG1 and IgG3 are the predominant subclasses associated with graft rejection and graft loss.…”
Section: Hla Antibody Subclassmentioning
confidence: 99%
“…This stratification and classification of DSA can be even further enhanced by DSA sub-typing as some classes of antibody are more efficient at fixing complement than others (Zhang 2018 ). C1q binding donor-specific antibodies are closely associated with acute ABMR, more severe graft injuries, and early graft failure, whereas C1q nonbinding donor-specific antibodies correlate with subclinical or chronic ABMR and late graft loss (Ponsirenas et al 2018 ).…”
Section: The Burden and Cost Of Allograft Rejectionmentioning
confidence: 99%